Credit risk in emerging markets Peruvian listed company - Burneo Farfan, Kurt (2017)
The aim of this paper is to introduce the importance of the banking credit risk, the main elements that conform it and the main alternatives that are offered to access to a loan as well as a description of its measurement and management in the sector. There will be a general explanation of credit risk and the main parties involved in it. As the topic is developed it is going to be analyzed the lending process carried out by the banks as well as the quantitative and qualitative elements taken into account when taking a credit decision (The 5C’s of credit, credit scoring and models for quantification of losses for instance). Another thing to considerate is that Credit risk arises whenever a borrower is expecting to use future cash flows to pay a current debt. Also, the investors have the access for the information of a client and they are compensated for assuming credit risk by way of interest payments from the borrower or issuer of a debt obligation and the credit risk is a useful tool for the finance management. The Enterprise risk management in Peru changed in 2015 because the local regulator is in process to review the norm, including some aspects of corporate governance; these changes are not included in this research.